Wir Kinder. La questione del potere nelle relazioni adulti/bambini - Spinosi, Nicola (Strumenti per la didattica e la ricerca, 2004)
The relationships between adults and children requires the presence of two parties involved, but one of the two, the children, has all the rights on their side, while the other, the parents, the adults, has all the duties and many responsibilities towards the first. "Who has the power?". This is the question around which the essays in this volume revolve: they are dedicated to the analysis of the relationships between adults and children as a question of "power", considered on Foucault's basis not as something that is shared between those who possess it and those who suffer it, but as something that "circulates". The analysis is carried out not only through the work of childhood and family historians, the critique of Freudian psychoanalysis, and Gregory Bateson's theory on the "double bind", but above all through the reading of works of Italian (Collodi, De Amicis, Vamba) and foreign fiction (Flaubert, Kafka, Bernhard).